PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA KONDISI HIPOKSIA YANG DIBERI PUPUK DAUN DAN ZAT PENGATUR TUMBUH - Sari, Muspika Sari; Tabrani, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The aims of this research is to improve the growth of seedlingspalm oil (Elaeis guineensis Jacq.) under hypoxia by applying foliar fertilizers and growth regulators. This research was conducted at experimental field of the Faculty of Agriculture, Universitas Riau from July to November 2019. The study was conducted with a split plot design in simple pattern in three replication. The main plots were foliar fertilizer kind (D), consisting of: d1 = organic liquid foliar fertilizer, d2 = inorganic granular foliar fertilizer, and d3 = inorganic liquid foliar fertilizer. The subplots were growth regulators kind (Z), which consisted: z1 = auxin, z2 = cytokinin, and z3 = gibberellins. The variable observed were: seedling height, number of leaf midribs, tuber diameter, root shoot ratio, seedling dry weight, and seedling quality index. The data analyzed of variance, and continued by orthogonal contrast test at 5%. The results showed, no interaction between foliar fertilizers and growth regulators on all growth components of oil palm seedling in hypoxia, but foliar fertilizer affects to the dry weight of the seeds and the seed quality index, which the inorganic foliar fertilizer does increased the seedling dry weight, and seedling quality index.Â Keywords: Palm oil seedlings, hypoxia, leaf fertilizer and growth regulators.